Modulated waves patterns in the photovoltaic photorefractive crystal - Dikwa, Jerome; Houwe, Alphonse; Abbagari, Souleymanou; Akinyemi, Lanre; İnç, Mustafa (Springer, 2022)
In this paper, we investigated the propagation of the modulated waves (MWs) patterns with the effects of the external field (EF) in a photorefractive crystal. To do so, we use the coupled nonlinear Schrodinger equations and we apply the auxiliary equation method to point out four families of solutions such as bright, dark, combined bright-dark, and bright-bright soliton. We pointed out the effects of EF on the modulation instability growth rate. Throughout the numerical simulation, we show that EF can generate MWs patterns when the short and open circuit condition is considered in the case of bright soliton. However, when we consider dark soliton solution as an initial condition and we have only obtained the MW pattern in the case of a short circuit. It results in this study of the propagation of the MWs patterns and chaos-like motion for specific cell indexes.
Keywords: Coupled nonlinear Schrodinger equations; Modulated waves patterns; Photorefractive crystal; External field; Solitons